If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2(x) = 3(x) + -2 Reorder the terms: 5 + 2x = -2 + 3x Solving 5 + 2x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 2x + -3x = -2 + 3x + -3x Combine like terms: 2x + -3x = -1x 5 + -1x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -1x = -2 + 0 5 + -1x = -2 Add '-5' to each side of the equation. 5 + -5 + -1x = -2 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -2 + -5 -1x = -2 + -5 Combine like terms: -2 + -5 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 0.6=0.5+25 | | 0.25X+0.35Y=6.4 | | 15-9x/3 | | 8-0.6+8= | | 9=n/m | | 1n+1m=x | | f(6)=4x-10 | | 4a+7=2a | | 2x-14+4=10 | | B=540-30*m | | 1x+2y+3z=34 | | X^2-10=11 | | (2x+50)+x+x=180 | | X^2=a^2 | | 4x+11=20-2 | | 5x=560+1.04x | | 4x^3-6x^3-2x+5=0 | | x^2+(x^2+2)=100 | | 12-10z+5x=-18 | | -15+3c-7c=-43 | | log(2x+1)log(2x-1)=1 | | 10=-7v+4(v+4) | | log(2x-12)=4 | | 2d+8=32 | | 4x-3+3=1+3 | | -9x+45-10+x=35 | | 2x+22=4x+13 | | -10z-5z=45 | | 3k+4=23 | | -5a+13a=64 | | 26.55=4x+18.75 | | 16/9=8x |